A study on ornamentation in the Putra Mosque of Putrajaya / Siti Nur Syahirah Nor Azlan - Nor Azlan, Siti Nur Syahirah (2019)
Throughout history, Islamic Ornamentation was the foremost characteristic to spot Muslims design. It utilized in mosques and different Muslims buildings. Several studies were concerning the formation of Muslims art from pre-existing ancient components and concerning the character of the ability that moulded all those varied components into a singular synthesis. Ornamentation is that the key part that's utilized in the most house of worship everywhere the planet. Ornamentation generally is well-known and used since the pre-historic era. Individuals at that point embellish their spiritual monument like a temple with some image of their belief. The ornamentation product of every ‘era is often had completely different background and purpose. Ornamentation in Muslims building has recorded in several books. Nowadays, the ornamentation in several mosques found has imitation problems. The aim of this study is to contextualize the idea and analyse the Muslims ornamentation in Putra Mosque of worship. The second step is concerning suggesting a number of the Muslims discipline components as new decorative components that have the identical result among the limit of Muslims ideology and principles, so as to gift new ornamentation components.